Morphological Factors that Underlie Neural Sensitivity to Stimulation in the Retina. Issue 12 (1st September 2021) - Raghuram, Vineeth; Werginz, Paul; Fried, Shelley I.; Timko, Brian P.
Abstract : Retinal prostheses are a promising therapeutic intervention for patients afflicted by outer retinal degenerative diseases such as retinitis pigmentosa and age‐related macular degeneration. Although significant advances in the development of retinal implants have been made, the quality of vision elicited by these devices remains largely suboptimal. The variability in the responses produced by retinal devices is most likely due to the differences between the natural cell‐type‐specific signaling that occur in the healthy retina versus the nonspecific activation of multiple cell types arising from artificial stimulation. To replicate these natural signaling patterns, stimulation strategies must be capable of preferentially activating specific retinal ganglion cell (RGC) types. To design more selective stimulation strategies, a better understanding of the morphological factors that underlie the sensitivity to prosthetic stimulation must be developed. Herein, the role that different anatomical components play in driving the direct activation of RGCs by extracellular stimulation is focused on. Briefly, 1) the variability in morphological properties of α‐RGCs is characterized, 2) the influence of morphology on the direct activation of RGCs by electric stimulation is detailed, and 3) some of the potential biophysical mechanisms that could explain differences in activation thresholds and electrically evoked responses between RGC types are described. Abstract : To design improved stimulation strategies that achieve selective activation of specific retinal ganglion cell (RGC) types, a better understanding of the morphological and biophysical factors that underlie the sensitivity and response of RGCs to prosthetic stimulation needs to be developed. Herein, studies that have investigated the role that the somatodendritic morphology and the axon initial segment play in driving the direct activation of RGCs by extracellular stimulation are focused on.